Religia – religijność – duchowość: Przemiany zjawiska i ewolucja pojęcia = Religion - Religiosity - Spirituality : Changes in the Phenomenon and Evolution of the Concept - - Motak, Dominika (Studia religiologica, 2010)
An effect of the revision of the secularisation thesis is an array of conceptions attempting to capture the essence of the modern transformations of religions and the shape of non-traditional forms of religiosity. The concept of „(new) spirituality”, which is supposed to signal a new religious megatrend, today aspires to the role of „universal key” to contemporary analysis of religion. The aim of this article is to attempt to clarify the meaning of this term by reconstructing the origins of spirituality - the phenomenon itself as well as the term used to describe it. The concepts used to describe this subject are ordered in the sequence religion - religiosity - spirituality, which also corresponds to the direction of religious transformations in the West. The course of these changes is presented in a three-phase model of the origins of new spirituality based on the metaphor of change of the concentration of religious material: from the solid body, via fluid form to a gaseous state. This model is diachronic in character, but is also a reflection of synchronic order (the spectrum whose poles correspond to traditional religion and new spirituality).